Ariel crashes a train - Cole, Olivia A. (Labyrinth Road, 2024)
Ariel grapples with her fear of her own mind and violent fantasies, driven by her desire to meet her parents' expectations and societal norms, until a summer job at a carnival leads her to new friends who help her discover her struggle with Obsessive Compulsive Disorder and find acceptance and support for her true self.